2018
DOI: 10.1139/cjc-2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations into the synthesis and antimicrobial activities of boron-containing capsaicinoids

Abstract: This preliminary study reports on the synthesis of two new boron-capsaicin derivatives containing either a short or long chain aliphatic tail group using an iridium catalyzed hydroboration reaction with pinacolborane. The boronate ester groups reside on the terminal position of the tail group and are necessary for the bioactivity of these compounds. Indeed, both compounds showed considerable activity against two Gram-positive bacteria, including Vancomycin-resistant Enterococcus. Vancomycin is considered the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Our desboro-aryl amine substrates either were unsubstituted (16) or bore aliphatic chains (17,18). We have previously found that increasing the length of aliphatic substituents on our boron-containing capsaicinoids provided greater antimicrobial activity, 36 and so functionalization at this position provided an opportunity to further tune the lipophilicity of the capsaicinoid. Amines 16-18 were isolated in modest to good yield.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our desboro-aryl amine substrates either were unsubstituted (16) or bore aliphatic chains (17,18). We have previously found that increasing the length of aliphatic substituents on our boron-containing capsaicinoids provided greater antimicrobial activity, 36 and so functionalization at this position provided an opportunity to further tune the lipophilicity of the capsaicinoid. Amines 16-18 were isolated in modest to good yield.…”
Section: Resultsmentioning
confidence: 99%
“…*Data collected in previous study, inhibition above 400 μM was considered inactive; activity against S. warneri was not previously studied. 36 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations